Handbook on the geopolitics of business - edited by Joseph Mark S. Munoz (Cheltenham Edward Elgar, 2013)
In recent years, rapid globalization, novel technologies and business models, as well as economic and political changes have transformed the international business landscape. This pioneering volume offers a comprehensive discussion of the new global terrain and makes a strong case for the consideration of geopolitics in both the study and practice of modern-day business.
Includes bibliographical references and index.
Keywords: Business and politics